Зміст міфологічної складової перекладацької компетенції (антична міфологія) - Варенко, Т.К. (СумДУ, 2005)
The aim of this article is to determine the content of the background knowledge required for the interpreter to deal with antique mythology-related allusions, texts and related classification as well as their implementation in the interpretation itself. The content of the antique mythology as an interpreter’s competence component consists of the following elements: antique gods’ pantheon, their functions and relations; antique heroes’ classification by their most prominent deeds; myths typology by their plots; mythological creatures’ systematization; divine attributiveness of the animal and plant worlds and constellations mythological origin.
Метою даної статті є визначення змісту фонових знань, які необхідні перекладачеві для роботи в галузі античної міфології та фольклору, та їх класифікація. Можна визначити наступні елементи змісту античної частини міфологічної складової перекладацької компетенції: пантеон богів, їх функції та взаємозв’язки, класифікація героїв за найвидатнішими їх подвигами, типологія міфів за сюжетами, систематизація міфологічних істот, божественна атрибутивність тваринного та рослинного світу та міфологічне походження сузір’їв.
Keywords: перекладацька компетенція; фонові знання; міфологічна складова